2004
DOI: 10.1021/ac0489420
|View full text |Cite
|
Sign up to set email alerts
|

Specific Method for the Determination of Genomic DNA Methylation by Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry

Abstract: Herein we report a novel method for determining genomic DNA methylation that utilizes liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) to measure 5-methyl-2'-deoxycytidine levels following enzymatic hydrolysis of genomic DNA. LC separation of 5-methyl-2'-deoxycytidine from the four deoxyribonucleosides, the four ribonucleosides, and 5-methyl-2'-cytidine, a RNA methylation product, has been achieved within 15 min. In combination with ESI-MS/MS detection, the reported method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
218
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(220 citation statements)
references
References 41 publications
1
218
1
Order By: Relevance
“…For this task, we utilized a genetic DNMT knockout HCT116 model system (Rhee et al, 2000(Rhee et al, , 2002. We initially confirmed the genotype and phenotype of the DNMT knockout lines by measuring DNMT1 and DNMT3b expression by Western blot and reverse transcriptase-polymerase chain reaction (RT-PCR), respectively (Supplemental Figure 2a and b), and by analysing global genomic DNA methylation levels using Liquid chromatography-mass spectrometry (LC-MS) (Song et al, 2005) (Supplemental Figure 2c). The LC-MS assay revealed that genomic 5mdC levels are moderately depressed (B20%) in DNMT1À/À cells, slightly reduced in DNMT3bÀ/À cells (B2%), and greatly reduced (B70%) in double knockout cells (DKO) (Supplemental Figure 2c), indicating that the two enzymes cooperate to maintain genomic DNA methylation (Rhee et al, 2002).…”
Section: Activation Of Cg-x Gene Expression By Genetic Knockout Of Dnmentioning
confidence: 99%
See 3 more Smart Citations
“…For this task, we utilized a genetic DNMT knockout HCT116 model system (Rhee et al, 2000(Rhee et al, , 2002. We initially confirmed the genotype and phenotype of the DNMT knockout lines by measuring DNMT1 and DNMT3b expression by Western blot and reverse transcriptase-polymerase chain reaction (RT-PCR), respectively (Supplemental Figure 2a and b), and by analysing global genomic DNA methylation levels using Liquid chromatography-mass spectrometry (LC-MS) (Song et al, 2005) (Supplemental Figure 2c). The LC-MS assay revealed that genomic 5mdC levels are moderately depressed (B20%) in DNMT1À/À cells, slightly reduced in DNMT3bÀ/À cells (B2%), and greatly reduced (B70%) in double knockout cells (DKO) (Supplemental Figure 2c), indicating that the two enzymes cooperate to maintain genomic DNA methylation (Rhee et al, 2002).…”
Section: Activation Of Cg-x Gene Expression By Genetic Knockout Of Dnmentioning
confidence: 99%
“…Wild-type, DNMT1À/À, DNMT3bÀ/À, and DNMT1/3b double knockout (DKO) HCT116 colorectal cancer cell lines were a generous gift from Dr Bert Vogelstein (Johns Hopkins University School of Medicine), and were cultured as described previously (Song et al, 2005). The colon adenocar-cinoma cell line RKO was obtained from the ATCC (Rockville, MD, USA), and was cultured as described previously (Karpf et al, 2001).…”
Section: Cell Culture and Drug Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were then compared to a set of standards with known methylation levels (Reddy and Reddy 1990;Fuke et al 2004). Updates to this method include replacing UV detection with mass spectrometry (Song et al 2005). For more simple assays, enzyme-linked immunosorbent assays (ELISA) use antibodies that are specific for mC or hmC with an in vitro generated standard curve to measure the global levels of methylation in a given sample (Kalani et al 2014).…”
Section: Historical Methods For Analysis Of Dna Modificationsmentioning
confidence: 99%